PENGARUH STRATEGI PEMASARAN PENDIDIKAN DAN MINAT LANJUT STUDI TERHADAP PENERIMAAN MAHASISWA BARU - Nduru, Martinus; Harefa, Chornelia Manisdar; Simanjuntak, Owen De Pinto (JURNAL MUTIARA MANAJEMEN, 2023)
The purpose of this study is to ascertain how study interest and educational marketing strategy affect the admission of new students to Yayasan Sauri Mitra Utama Medan in 2023. The results of this study are partial and concurrent, but they are favorable and substantial. A qualitative approach is the research methodology employed. The sample method involves giving a list of questions or a Likert scale, which is a measuring scale, and the data gathering method uses a questionnaire utilizing a Google Form. A set of questions that have been meticulously prepared beforehand is provided via questionnaires, which are used to collect data. The analytical method used is validity test, reliability test, classical assumption test, and hypothesistest. Both partially and simultaneously, the findings of this study, " Yayasan Sauri Mitra Utama Medan's new student admissions in 2023 are positively and significantly impacted by educational marketing strategy and interests in continuing education. The obtained R square value is 42.3%, or 0.423×100. This indicates that 42.3% of respondents at Yayasan Sauri Mitra Utama Medan cited educational marketing strategy and interest in furthering their education when deciding whether to admit new students, with the remaining 57.7% citing factors unrelated to this study.